Deepening the Relationship between Diabetes, Oral Health and Severity of Periodontal Diseases in Pakistani Population - Kashif Adnan, Sheharyar Abid, Shahrukh Irfan, Zainab Khan, Sughra Abid, Amna Arif (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: This study aimed to understand the connection between diabetes, oral health, and the severity of periodontal disease within the Pakistani populace. Its intention was to bring forth insights that would contribute to enhancing health outcomes and the quality of life for diabetic individuals in Pakistan. Method: A quantitative research approach was adopted, leveraging SPSS for data analysis. The study was built on secondary data gathered from an ensemble of 1,000 individuals. Findings: The analysis showed that there was no significant association between diabetes status and the severity of periodontal disease (χ² = 2.171, df = 2, p = .338). Furthermore, age was not significantly related to periodontal severity (r = .012, p = .709). Practical Implication: Despite the absence of a significant relationship between diabetes, age, and periodontal severity, the study underscores the need to monitor oral health vigilantly in diabetic patients. Healthcare professionals, policymakers, and public health specialists can harness this information to devise tailored strategies aimed at enhancing oral health and managing diabetes more effectively in Pakistan. Conclusion: While there wasn’t a notable relationship between diabetes and periodontal severity in this study, the investigation undeniably points towards the importance of focused interventions in oral health for diabetic individuals. The absence of a significant connection prompts the exploration of other potential determinants influencing oral health in diabetic individuals. This research lays the groundwork for future studies in the domain of oral health and diabetes. Keywords: Diabetes, Oral Health, Periodontal Disease, Pakistani Population, Health Interventions, Quantitative Analysis.